การใช้ยาเฮปารินด้วยวิธีเวทเบสเฮปารินนอมอแกรมเปรียบเทียบกับการใช้ยาด้วยวิธีมาตรฐาน โดยอาศัยระดับของซีรัมเอพีทีทีในผู้ป่วยของหอผู้ป่วยหนักโรงพยาบาลจุฬาลงกรณ์ - สมศักดิ์ เอกปรัชญากุล (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
The efficiency of time to achieve therapeutic anticoagulant with heparin in Thai patients using two heparin-dosing methods has been studied. Because the action of heparin is dependent on many in vivo protein factors, it is difference from race to race, and no previous research about weight-based heparin nomogram in Thai patients had been studied What the exact result, when heparin based on body weight is used, are being determined. A randomized controlled trial of sixty-nine Thai patients in the intensive care units of King Chulalongkorn Memorial Hospital, who had the indication for treatment with heparin, were randomized to the standard method or the weight-based heparin nomogram method. During November 1, 1998 thought March 15, 1999, 34 patients received the standard method and 35 patients received the weight-based heparin nomogram. The every six-hour serum APTTs was measured for heparin dosing adjustments. The serum APTT level between 1.5-2.5 times of controlled valued was set as achieved the therapeutic level. Interestingly, 45.5% of the patients in the weight-based heparin nomogram achieved the therapeutic level compared to the 15.2% of the standard method at the 12th hour (p = 0.007). Likewise, at the 18th hour and the 24th hour also had the better efficiency of weight-based method by 48.6% vs. 18.2% and 48.6% vs. 25.0% (p = 0.008 and p = 0.046) respectively. In conclusion, use of a weight-based heparin nomogram in Thai critical filed patients was more effective in achieved early therapeutic level compared to the standard one.